Dispelling myths: Christian prayers and their impact on democracy building in Nigeria - Chisom B. Amaole (African Journal of Pentecostal Studies)
Background: Prayer and political participation are two important elements of the Christian faith and the state. However, the importance of prayer in democracy-building is one that is widely misconstrued among Christians in Nigeria. Lack of adequate knowledge of the role of prayer and political participation often generates false traditional conceptions that undermine democracy-building through collective political participation.